Answer:
3y = -2x + 1
Step-by-step explanation:
Equation of given line is 2y = 3x + 2
==> y = (2/2)x + 1
Slope = 3/2
Slope of perpendicular line is negative of reciprocal of given line ie slope = -2/3
So equation of perpendicular line is of the form
y = (-2/3)x + c where c is a constant
Given that this passes thru x= -1, y =1 we can substitute these values in the above to get
1 = (-2/3)(-1) + c
This yields 1 = (2/3) + c or c = 1-2/3 = 1/3
So the equation of the perpendicular line is
y = (-2/3)x + 1/3
3y = -2x + 1